Editorial - Kouis, Dimitris (Journal of Integrated Information Management, 2019)
The main theme of the first article concerns academic libraries’ adaptation in the ongoing technological and management innovation. This is a meaningful contribution to the local and international library and information community’s deeper understanding of the factors that hinder or foster Hellenic Academic Libraries’ adaptation to the information society’s demands. The next article presents and discusses useful findings of the perception and the implications of Plagiarism, derived from a survey that was conducted in 2018, in undergraduate students and academic staff. Plagiarism is one of the main aspects that Information Literacy (IL) seeks to face. Therefore, the third article is dedicated to an IL Service SWOT analysis, recording a real story of an IL Service development deepening in design, implementation, evaluation, successes and failures. The article concludes by proposing better practices that urge Hellenic Academic Libraries to create from scratch their own IL Services or to develop their existed ones further. Next article is about different efforts exerted on the acquisition and preservation of industrial archives in Greece, aiming to uncover the challenges that new archivists may encounter. The final article focuses on the Department of Archives, Library and Information Studies of the University of West Attica curriculum reform. Specifically, the courses program expanded to meet the informational needs of cultural heritage institutions, such as museums and cultural centres, concerning the interrelationship of the Horizon2020 Project “CrossCult”, in which the Department mentioned above participated.